The Effect of Urtica Dioica Extracts on Third Larval Instars of Tribolium Confusum (DU VAL) Using Two Methods of Extraction - Rasheed, Mehvan M. Ali; Al-Chalabi , Badia’a Mahmoud; Al-Sinjari , Sofyan H. Sedo (Science Journal of University of Zakho, 2022)
The effect of ethanolic extracts of Urtica dioica on mortality of the third Larval instar of Tribolium confusum, was studied using the Soxhlet and solvent extraction methods. Experiments at 30 ± 1°C and 70 ± 5% relative humidity. In laboratory conditions. The mortality data were recorded after 24, 48, and 72 hours. The mortality rate increased by an increase in concentrations (0.5, 1, 1.5, and 2.5 mg/ml), the highest mortality rate was 100% at 1.5 mg/ml, while the lowest percentage of mortality 73.33% was observed after 24 hrs of exposure at 0.5 mg/ml dose by Soxhlet extraction method, whereas the highest mortality rates 100% at 2.5 mg/ml concentration, while the lowest percentage of mortality 90% was observed after 24 hrs of exposure at 0.5 mg/ml dose by Solvent extraction methods. The results show that the plant extracts tested at different concentrations were toxic to the larvae of T. confusum, and both methods of extraction had nearly similar effects on larvae.